Emotional distress and psychiatric drug use among students in an Italian medical school: Assessing the role of gender and year of study - Sara Carletto; Marco Miniotti; Alberto Persico; Paolo Leombruni (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Previous studies have reported that medical students show high rates of depression, anxiety, and stress levels, but mixed findings were found regarding possible differences between gender and different years of medical training. This study evaluated depression, anxiety, and stress levels and psychiatric drug use in students in an Italian medical school and investigated the differences between gender and year of study. MATERIALS AND METHODS: This cross-sectional study included 694 medical students in their 1st (n = 286), 4th (n = 209), and 6th (n = 199) year of study. The questionnaire included demographic information, self-report questionnaires regarding depression, anxiety, and stress, and questions about psychiatric drug use. Data analysis was performed using SPSS/Ver 22 through descriptive and analytic statistics, including Mann-Whitney U-test, Fisher's exact test, and GLM two-way ANOVA. RESULTS: Depression, anxiety, and stress symptoms were reported by 365 (52.6%), 428 (61.7%), and 545 (78.5%) medical students, respectively. Female students in their 4th year of study reported higher depression levels than males of the same year (P = 0.004), whereas levels of anxiety were higher in 6th-year female students compared with those in their 1st and 4th years (P = 0.001; P = 0.025). Stress levels were consistently higher in females than in males for all 3 years (1st year: P = 0.041; 4th year: P < 0.001; 6th year: P = 0.004). No gender differences were found in the use of psychiatric and stimulant drugs. CONCLUSION: This study provides preliminary evidence suggesting the importance of planning interventions aimed at reducing emotional distress among medical students that should be targeted on gender and year of the study.